The Role of Women in the Rukyat Hilal According to the North Aceh Ulema Consultative Assembly - Machzumy Machzumy; Badrun Taman (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2022)
The Role of Women in Rukyat Hilal According to the North Aceh Ulema Consultative Assembly (MPU). Rukyat hilal is a method used to determine the beginning and end of the month of Kamariah. And along with the birth of the Falak Science study program in Indonesia, many also mastered falak science. One of the interesting things is the existence of female phallic experts and their role in determining the beginning of the Hijri month. This rukyat hilal activity is carried out collectively by the Ministry of Religious Affairs, the Ulema Consultative Assembly, BMKG and other community groups. From this background, the author is interested in studying the role of women in seeing hilal in North Aceh Regency based on the perspective of MPU. This research is a qualitative research, with a field approach (field research). The data collection method uses interview and documentation techniques. The results of this study show that the role of a woman in determining the beginning and end of the month in North Aceh according to the Majelis Permusyawaratan Ulama Aceh Utara there are two. First, if a woman is only a participant who participates in the Rukyat Hilal event, then this is allowed. Second, if a woman reports seeing hilal, then her testimony is not considered valid and rejected.